Giving combined medium‐chain fatty acids and glucose protects against cancer‐associated skeletal muscle atrophy - Mori, Takuya (Cancer Sci, 2019)
Skeletal muscle volume is associated with prognosis of cancer patients. Maintenance of skeletal muscle is an essential concern in cancer treatment. In nutritional intervention, it is important to focus on differences in metabolism between tumor and skeletal muscle. We examined the influence of oral intake of glucose (0%, 10%, 50%) and 2% medium‐chain fatty acid (lauric acid, LAA, C12:0) on tumor growth and skeletal muscle atrophy in mouse peritoneal metastasis models using CT26 mouse colon cancer cells and HT29 human colon cancer cells. After 2 weeks of experimental breeding, skeletal muscle and tumor were removed and analyzed. Glucose intake contributed to prevention of skeletal muscle atrophy in a sugar concentration‐dependent way and also promoted tumor growth. LAA ingestion elevated the level of skeletal muscle protein and suppressed tumor growth by inducing tumor‐selective oxidative stress production. When a combination of glucose and LAA was ingested, skeletal muscle mass increased and tumor growth was suppressed. Our results confirmed that although glucose is an important nutrient for the prevention of skeletal muscle atrophy, it may also foster tumor growth. However, the ingestion of LAA inhibited tumor growth, and its combination with glucose promoted skeletal muscle integrity and function, without stimulating tumor growth. These findings suggest novel strategies for the prevention of skeletal muscle atrophy.